Setze in den Term %%T(x)=\left(\frac14-x+x^2\right):\left(-\frac12\right)%% für die Variable %%x%% die Zahlen %%-2; -1; -0,50; 0,25;%%  %%\frac34%% sowie 1 ein und berechne die zugehörigen Termwerte.

%%x%%

-2

-1

-0,5

0,25

%%\frac{3}{4}%%

1

%%T(x)%%

-12,5

-4,5

-2

-0,125

-0,125

-0,5

für %%x=-2%%

%%\left(\frac14-x+x^2\right):\left(-\frac12\right)=%%

%%x=-2%% einsetzen.

%%=\left(\frac14-\left(-2\right)+\left(-2\right)^2\right):\left(-\frac12\right)%%

%%=\left(\frac14+2+4\right):\left(-\frac12\right)%%

Hauptnenner bilden. %%\rightarrow\;4%%

%%=\left(\frac14+\frac84+\frac{16}4\right):\left(-\frac12\right)%%

%%=\frac{25}4:\left(-\frac12\right)%%

%%=\frac{25}4\cdot\left(-\frac21\right)%%

%%=-\frac{25}2=-12,5%%

für %%x=-1%%

%%\left(\frac14-x+x^2\right):\left(-\frac12\right)=%%

%%x=-1%% einsetzen.

%%=\left(\frac14-\left(-1\right)+\left(-1\right)^2\right):\left(-\frac12\right)%%

%%=\left(\frac14+1+1\right):\left(-\frac12\right)%%

Hauptnenner bilden. %%\rightarrow\;4%%

%%=\left(\frac14+\frac44+\frac44\right):\left(-\frac12\right)%%

%%=\frac94\cdot\left(-\frac21\right)%%

%%=-\frac92=-4,5%%

für %%x=-0,5%%

%%\left(\frac14-x+x^2\right):\left(-\frac12\right)=%%

%%=\left(\frac14-\left(-0,5\right)+\left(-0,5\right)^2\right):\left(-\frac12\right)%%

%%=\left(\frac14+0,5+0,25\right):\left(-\frac12\right)%%

%%=\left(\frac14+\frac24+\frac14\right):\left(-\frac12\right)%%

%%=\frac44\cdot\left(-\frac21\right)%%

%%=-\frac42=-2%%

für %%x=0,25%%

%%\left(\frac14-x+x^2\right):\left(-\frac12\right)=%%

%%=\left(\frac14-\left(0,25\right)+\left(0,25\right)^2\right):\left(-\frac12\right)%%

%%=\left(\frac14-0,25+0,0625\right):\left(-\frac12\right)%%

%%=\left(\frac14-\frac14+0,0625\right):\left(-\frac12\right)%%

%%= \left(\frac{1}{16}\right):\left(-\frac12\right)%%

%%= \left(\frac{1}{16}\right)\cdot\left(-\frac{2}{1}\right)=\left(-\frac18\right)=-0,125%%

für %%x=\frac34%%

%%\left(\frac14-x+x^2\right):\left(-\frac12\right)=%%

%%=\left(\frac14-\left(\frac34\right)+\left(\frac34\right)^2\right):\left(-\frac12\right)%%

%%=\left(\frac14-\frac34+\frac9{16}\right):\left(-\frac12\right)%%

%%=\left(\frac4{16}-\frac{12}{16}+\frac9{16}\right):\left(-\frac12\right)%%

%%=\frac1{16}\cdot\left(-\frac21\right)=\left(-\frac18\right)=-0,125%%

für %%x=1%%

%%\left(\frac14-1+\left(1\right)^2\right):\left(-\frac12\right)=%%

%%=\left(\frac14\right):\left(-\frac12\right)%%

%%=\frac14\cdot\left(-\frac21\right)=-0,5%%